Gerakan Cemilan Sehat Berbasis Nanas dan Kacang Tanah untuk Mengurangi Konsumsi Jajan Anak dalam Mencegah Stunting di Desa Kaenbaun, Kabupaten Timor Tengah Utara - Gudino, Isabel De Fatima; Lamak, Maria Rovina J.; Simbolon, Meteria; Sembiring, Tiarmawati (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Stunting is a chronic nutritional problem that remains a major public health challenge, particularly in rural areas with limited access to nutritious food and information. One contributing factor is the high consumption of processed snacks and junk food with low nutritional value among children. This community service activity aimed to improve the knowledge and skills of mothers and community health cadres in reducing unhealthy snack consumption through a healthy snack movement based on local food ingredients. The activity was conducted in Kaenbaun Village, North Central Timor Regency, using nutrition education sessions, hands-on practice in making healthy snacks from peanuts and pineapple, and continuous mentoring. The results indicated increased participant awareness of the risks of processed snacks and the importance of balanced nutrition for children. Participants were able to independently prepare healthy snacks, demonstrated strong enthusiasm, and applied food hygiene and safety principles at community level.